CONCEPTUAL CATEGORY PERSON AND MEANS OF ITS VERBAL PRESENTATION IN THE FANTASY GENRE - Aleksandruk, Iryna; Babelyuk, Oksana (Advanced Education, 2018)
The studies devoted to the issues of conceptualisation and categorisation of reality prove that language plays a key role in these two interrelated and interdependent processes. The purpose of the article is to analyse the structure of the conceptual category PERSON and the means of its verbal presentation in the fantasy genre. The data is collected from 85 fantasy novels written by British and American writers within the period from 1997 to 2012. The data includes 5890 nominative units (innovations, phrases, word combinations, sentences) either to name or characterise people of possible worlds presented in fantasy novels. The methods applied in this research are chosen considering the aim, objectives, and data. The contextual analysis, the analysis of definitions provided in the lexicographical sources and fantasy texts, and the morphemic analysis are used to analyse the data collected. According to the results of the research, the conceptual category PERSON has a complex hierarchical structure. Two sub-categories – the Name of a Person and the Group of People – are determined in the structure of this conceptual category. The sub-category Name of a Person comprises about 63% (3730) of nominative units. Innovations are created by the writers to name or describe people of possible worlds, which comprise 79% (4653) of all the data collected. Peculiar features of fantasy discourse, in general, may be the focus of further research. It is also planned to contribute to online dictionaries devoted to fantasy novels.